Lecturers’ and Students’ Acceptance of Using Technology-Based Teaching AIDS (TTAs) When Teaching Ulum Hadith During the Covid-19 Pandemic - Ahmad, Khalilullah Amin; Abdul Hamid, Solahuddin; Abdul Rahman, Mohd Nizho (Pegem Akademi Yayincilik Egitim Danismanlik Hizmetleri Ticaret A.S., 2022)
The COVID-19 Pandemic poses new challenges to those who intend to adopt a new teaching norm based on online learning. Some of the mediums involved in technology-based teaching aids (TTAs) are Google Meet, Google Classroom, Zoom Meetings, Microsoft Teams and Webex Meeting by CISCO. This study aims to examine the acceptance of lecturers and students on the use of TTAs during the Ulum Hadith course at several Institutes of Higher Learning (IHL) in Northern Malaysia. This qualitative design study only examined the implementation of online learning involving the Ulum Hadith course. Data were collected through interviews, observations and document analysis. The study sample comprised 13 lecturers, who acted as the main informants and 18 students from three IHL pursuing the Ulum Hadith course. Findings indicate a variety of TTAs were used during the teaching and learning sessions in order to attract the attention and active involvement of students during the pursuit of the Ulum Hadith course. Lecturers and students had a positive outlook towards TTA based on the increased frequency of TTAs used during the COVID-19 pandemic compared to before that period. Hence, it is suggested that lecturers should frequently update themselves on the latest developments in TTA so that the learning process occurs smoothly even though the world is presently faced with some challenging circumstances